Storage Characteristics and Shelf-life Prediction of Probiotic Fermented Kiwifruit Juice - Tian LAN; Qinyu ZHAO; Jiaqi WANG; Xiangyu SUN; Tingting MA (Shipin gongye ke-ji, 2024)
This study investigated the storage characteristics of probiotic fermented kiwifruit juice under 4 ℃ refrigeration. The research focused on the changes in the viable lactic acid bacteria count physicochemical properties, sensory quality, nutritional quality and functional properties of the juice during 14 days storage period. Additionally, preliminary shelf-life prediction was made based on the changes in ascorbic acid during the storage. The results showed that the fermented kiwifruit juice maintained good probiotic activity throughout the entire storage process with a consistently higher viable bacterial count of over 8.7 lg CFU/mL. Meanwhile, the fermented juice maintained stable physicochemical properties and color and odor characteristics during storage. Compared to unfermented juice, probiotic fermentation contributed to retaining and maintaining ascorbic acid, total phenols and antioxidant activity of juice during storage. In particular, the unfermented juice experienced a 67.98% loss in ascorbic acid after storage, while fermented juice only lost 23.94%. Moreover, based on the zero-order kinetic model, the study effectively predicted the changes in ascorbic acid in kiwifruit juice during storage. The prediction results indicated that fermented juice could be stored at 4 ℃ for 50 d, while unfermented juice could only be stored for 15 d, based on whether ascorbic acid could be effectively supplemented. This showed that fermented kiwifruit juice could maintain high nutritional quality for an extended period during cold storage, further providing the possibility for the commercialization of fermented kiwifruit juice.